Turkic Acculturation and the Emergence of Bengali Identity - Khan, Mohammad Mahmudul Hasan; Ahsan Habib; Abu B. Siddiq (CenRaPS Journal of Social Sciences, 2022)
Bengal is the largest delta in the world. Because of the easy access to natural wealth, many people groups of different ethno-religious backgrounds migrated into Bengal from prehistoric times. Following the conquest of Bengal by the Khalaj descended Muhammad bin Bakhtiyar Khalji, the Central and West Asian traditions greatly influenced the Delta throughout about 600 years. Although there were migrations of many other groups, primarily the predominance of Turkic traditions encouraged waves of Turk-Bengali acculturations which helped emerge and mature the Bengali identity in the Delta. Later, there were trends of false narration, propaganda history and attempts of deculturation throughout 190 year-long colonial rule. Yet, the signs of this harmonious and mutual acculturation still survive in archaeological and historical sources of the region. Citing some of them, this study aims to present a glimpse of the process of welfare and Turk-Bengal acculturation in the Bengal Delta.